Ladder approximation for the AC conductivity in the generalized two-dimensional Hubbard model. (May 2017) - Lima, L.S.
Abstract: We calculate the optical conductivity of the generalized two-dimensional Hubbard model including vertex corrections, by using a ladder approximation in the diagrammatic expansion. We have obtained a superconductor behavior for this system at low temperature. Employing the ladder approach, we have included the influence of the electron-electron interaction on a previous result obtained in the mean field approximation. We have obtained the behavior of the optical conductivity, employing the ladder approximation, tending to zero in the DC limit. Since this approximation is better than the mean field approximation (it include information about the electron-electron interaction) then we have a better description to the behavior of the AC optical conductivity for the two-dimensional Hubbard model. Highlights: The generalized two-dimensional Hubbard model is diagonalized and the single particle fermionic spectrum is obtained. The AC electric conductivity is calculated without the electron-electron interaction. The effect of the electron-electron scattering is included using the ladder approach.